Atypical reactive lymphoid hyperplasia : a 5 year study with analysis of 10 cases for latent Epstein-Barr virus infection by in situ hybridization and immunohistochemistry - Eedes, Christopher Robert; Eedes, Christopher Robert (Division of Anatomical Pathology, 2017)
AIMS OF THE STUDY: 1. To perform a retrospective, epidemiological analysis of cases of reactive lymphadenopathy and atypical reactive lymphoid hyperplasia (ARLH) received in the Department of Anatomical Pathology, UCT and GSH, over a 5 year period, in order to determine the number of cases of ARLH, and the frequency of the various subtypes of reactive lymphoid. hyperplasia, so as to provide base-line information for further studies. 2. To set up IN SITU HYBRIDIZATION (ISH) for detection of Epstein-Barr virus (EBV)-encoded RNA's (EBERs) in latently infected cells in selected cases, to determine if virus is present in ARLH. 3. To perform immunohistochemical analysis for the detection of EBY-derived latent membrane protein (LMP) in those cases subjected to ISH.